Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1016/j.yjsbx.2021.100044
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of enzyme activity regulation by the propeptide of l-lysine α-oxidase precursor from Trichoderma viride

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Biochemical, structural, and computational analysis of AncLLysO2 indicated that the enzyme is a less promiscuous l -Lys α-oxidase having no pro-sequence; LAAO activity is often toxic for living organisms, so to reduce the activity under in vivo conditions, several of the LAAOs hinder the substrate entrance pathway by the pro-sequence. , The properties were different from other LLysOs; catalytic promiscuity (oxidase and mono-oxygenase activity) was confirmed in AncLLysO and L-LOX/MOG, and l -Lys α-oxidase from Trichoderma viride (TvLysO) matured by cleaving the pro-sequence . Sequence identity among the enzymes was <32% (Table S4), suggesting that the enzymes have unique substrate recognition mechanisms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochemical, structural, and computational analysis of AncLLysO2 indicated that the enzyme is a less promiscuous l -Lys α-oxidase having no pro-sequence; LAAO activity is often toxic for living organisms, so to reduce the activity under in vivo conditions, several of the LAAOs hinder the substrate entrance pathway by the pro-sequence. , The properties were different from other LLysOs; catalytic promiscuity (oxidase and mono-oxygenase activity) was confirmed in AncLLysO and L-LOX/MOG, and l -Lys α-oxidase from Trichoderma viride (TvLysO) matured by cleaving the pro-sequence . Sequence identity among the enzymes was <32% (Table S4), suggesting that the enzymes have unique substrate recognition mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“… 44 , 45 The properties were different from other LLysOs; catalytic promiscuity (oxidase and mono-oxygenase activity) was confirmed in AncLLysO and L-LOX/MOG, and l -Lys α-oxidase from Trichoderma viride (TvLysO) matured by cleaving the pro-sequence. 46 Sequence identity among the enzymes was <32% ( Table S4 ), suggesting that the enzymes have unique substrate recognition mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…The l -lysine α-oxidase (LO) from Trichoderma harzianum is a flavoprotein from the family of l -amino acid oxidases (LAAOs) [ 32 ], an enzyme family extensively studied in medicine for their cytotoxic effects in different tumor cells. However, the large-scale expression and isolation in prokaryotic hosts such as E. coli [ 17 ] is a challenge for the development of commercial recombinant LAAOs, mainly due to the formation of inclusion bodies [ 33 ], production of the inactive [ 34 ], and/or low yield [ 35 ]. Another issue with the heterologous expression of these enzymes is that they are usually expressed as propeptide precursors to protect the host organism from the LAAO toxicity [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The L-lysine α-oxidase (LO) from Trichoderma harzianum is a avoprotein from the family of L-amino acid oxidases (LAAOs) [32], an enzyme family extensively studied in medicine for their cytotoxic effects in different tumor cells. However, a challenge for the development of commercial recombinant LAAOs is the large-scale expression and isolation in prokaryotic hosts such as E. coli [33], mainly due to the formation of inclusion bodies [34], production of the inactive [35], and/or low yield [51]. Another di culty in the heterologous expression is that they are usually expressed as propeptide precursors, rendering the host organism protection from the LAAO toxicity [36].…”
Section: Discussionmentioning
confidence: 99%